Respuesta :
Answer : [tex] 3a^3 - 6a^2 - 2 [/tex]
The variables X, Y, and Z represent polynomials where
X = a, Y = 3a – 5, and Z = [tex] a^2 + 2 [/tex]
We need to find [tex]X^2Y - Z [/tex]
We replace the values of X, Y and Z
[tex] X^2Y - Z[/tex] = [tex] (a)^2(3a - 5) - (a^2 + 2)[/tex]
Now we simplify it
[tex] (a)^2(3a - 5) - (a^2 + 2)[/tex] = [tex] 3a^3 - 5a^2 - a^2 - 2 = 3a^3 - 6a^2 -2 [/tex]
Answer:
The simplest form of [tex]X^2Y-Z[/tex] is [tex]3a^3-6a^2-2[/tex]
Option 2 is correct.
Step-by-step explanation:
Given: The variables X, Y, and Z represent polynomials.
[tex]X=a[/tex]
[tex]Y=3a-5[/tex]
[tex]Z=a^2+2[/tex]
We need to find [tex]X^2Y-Z[/tex]
Substitute the value of X, Y and Z into expression
[tex]\Rightarrow (a^2)(3a-5)-(a^2+2)[/tex]
[tex]\Rightarrow 3a^3-5a^2-a^2-2[/tex]
Combine the like term
[tex]\Rightarrow 3a^3-6a^2-2[/tex]
Simplest form is [tex]\Rightarrow 3a^3-6a^2-2[/tex]
Hence, The simplest form of [tex]X^2Y-Z[/tex] is [tex]3a^3-6a^2-2[/tex]